2010
DOI: 10.1093/mutage/geq039
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the genotoxic potential of indirect chemical mutagens in HepaRG cells by the comet and the cytokinesis-block micronucleus assays

Abstract: Many chemical carcinogens require metabolic activation to form genotoxic compounds in human. Standard in vitro genotoxicity assays performed with activation systems, such as rat liver S9, are recognised to lead to a high number of false positives. The aim of this study was to evaluate the suitability of differentiated human hepatoma HepaRG cells as an in vitro model system for the detection of DNA damage induced by promutagens using the comet and the cytokinesis-block micronucleus assays. Several promutagens w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(23 citation statements)
references
References 41 publications
3
20
0
Order By: Relevance
“…However, it should be noted that proinflammatory cytokines in rodent models usually cause downregulation of CYP2E1, emphasizing species-dependent differences (Siewert et al, 2000;Hakkola et al, 2003). The lack of inducibility of CYP2E1 in HepaRG cells is probably related to the generally low expression and may also depend on the culture conditions (Kanebratt and Andersson, 2008;Le Hegarat et al, 2010). Among further phase 1 genes, we found that mRNA expression of ADH1A, ALDH2, and DPYD was only moderately affected in both cell systems.…”
Section: Discussionmentioning
confidence: 81%
“…However, it should be noted that proinflammatory cytokines in rodent models usually cause downregulation of CYP2E1, emphasizing species-dependent differences (Siewert et al, 2000;Hakkola et al, 2003). The lack of inducibility of CYP2E1 in HepaRG cells is probably related to the generally low expression and may also depend on the culture conditions (Kanebratt and Andersson, 2008;Le Hegarat et al, 2010). Among further phase 1 genes, we found that mRNA expression of ADH1A, ALDH2, and DPYD was only moderately affected in both cell systems.…”
Section: Discussionmentioning
confidence: 81%
“…One of the main limiting factors is the high number of false positive results (Fowler et al, ) which is probably a consequence of underrepresentation of detoxifying enzymes in the currently available indicator cells. A possible solution is the use of specific human derived liver cell lines which have retained the activities of a variety of drug metabolizing phase I and II enzymes (Knasmuller et al, ; Winter et al, ; Le Hegarat et al, ). We showed in a recent investigation in single cell gel electrophoresis (SCGE) experiments (Waldherr et al, ) that the human liver line Huh6, which was never used in genotoxicity studies before, detects representatives of a broad variety of DNA reactive genotoxins which require metabolic activation.…”
Section: Introductionmentioning
confidence: 99%
“…B[a]P, at a concentration of 50 microg/ml, produced a signiWcant increase in the frequencies of chromosomal aberrations (CA) in human bronchial epithelial cells (Lee and Lee 1998). A dose-dependent increase in micronucleated cells was observed in diVerentiated human hepatoma HepaRG cells treated with B[a]P (Le Hegarat et al 2010). Warshawsky reported that the 5-ring polycyclic aromatic B[a]P could induce increased frequencies of micronuclei and SCE in a linear dose-dependent manner in cultured human lymphocytes (Warshawsky et al 1995).…”
Section: Introductionmentioning
confidence: 99%